Toxicity of fiber in chemi-thermomechanical pulp wastewaters to anaerobic bacteria: A batch assay and reactor study comparison. - Richardson, Debra Ann. (University of Ottawa (Canada), 1992)
Toxicity of chemi-thermomechanical pulping (CTMP) wastewaters was tested in batch assays and in two-stage anaerobic sludge blanket reactors. In batch serum bottle tests particulate constituents were responsible for 80-90% of the inhibition of acetoclastic activity and the soluble (fiber-free) fraction accounted for 10-20%. Performance of three two-stage anaerobic sludge blanket reactor systems was compared. One reactor received fiber-free, one received clarified, and the other unaltered wastewater for 140 days. All reactors became acclimatized to the CTMP and developed a tolerance to resin acid concentrations as high as 300 to 1500 mg/L in the sludge bed. The performance of the fiber-free system was superior throughout the experiment, but the difference in system performances did not reflect the batch test results. At an organic loading rate of 17-22 g soluble COD/g VSS$\cdot$d the fiber-free system treated 100% CTMP wastewater with 42% and the fiber system treated with 38% removal efficiency. Fiber accumulation in the sludge bed of the systems treating raw and clarified CTMP caused a 70% increase in bed volume, resulting in deterioration of sludge settleability and led to an increased likelihood of biomass loss.
Keywords: Engineering, Chemical.